PENGARUH MODEL PEMBELAJARAN TEAM ASSISTED INDIVIDUALIZATION TERHADAP KEMAMPUAN SERVIS BOLA VOLI PADA SISWA SMP AT-THOHARIYAH - Gunawan Gunawan; Irfan Zinat Achmad; Oktaviarini Yahya Rahmadhanty (Universitas Hamzanwadi, 2026)
This study aimed to determine the effect of the Team Assisted Individualization (TAI) learning model on volleyball service skills among students of SMP At-Thohariyah. The study employed a quantitative approach using a pre-experimental method with a one-group pretest-posttest design. The population consisted of eighth-grade students of SMP At-Thohariyah in the 2025/2026 academic year, while the sample was selected using a total sampling technique. Data were collected through volleyball service skill tests administered before (pretest) and after (posttest) the implementation of the TAI learning model. The collected data were analyzed using descriptive statistics, normality tests, homogeneity tests, and paired sample t-tests. The findings indicated that the implementation of the Team Assisted Individualization learning model significantly improved students' volleyball service skills. The collaborative learning process, which emphasizes peer assistance, individual responsibility, and group cooperation, enabled students to understand service techniques more effectively and improve their motor skills performance. Therefore, the Team Assisted Individualization learning model can be considered an effective and innovative learning alternative for improving volleyball service skills in physical education learning at the junior high school level.